Analysis of the Geiger Muller Ability on the Effect of Collimation Area and Irradiation Distance on the Dose of X-Ray Machine Measurements - Wahyu Pratama; Muhammad Ridha Mak'ruf; Tri Bowo Indrato; Endro Yulianto; Lamidi Lamidi; Maduka Nosike; Sambhrant Srivastava (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Radiation cannot be felt directly by the five human senses. For the occupational safety and security, a radiation worker or radiographer is endeavored to receive radiation dose as minimum as possible, which is by monitoring the radiation using a radiation measuring device. The purpose of this study was to analyze the effect of collimation area and irradiation distance on x-ray dose measurement using Geiger Muller. In this case, the author tried to make a dosimeter by using the Muller Geiger module and displayed it on a personal computer. This research employed Muller Geiger sensor to detect X-ray dose and velocity, Arduino for data programming, Bluetooth HC-05 for digital communication tool between hardware and personal computer, and personal computer to display the reading. Current research was conducted using Pre-Experimental research design. Based on the results of data collection and comparison with the standard tool, it can be concluded that the greater the tube current setting (mA), the greater the dose and rate of radiation exposure at a distance of 100cm with 50KV and 70KV settings, and a distance of 150cm with 50KV settings. However, it is inversely proportional to the measurement results at a distance of 150cm with a 70KV setting. The results of this study are further expected to determine the ability of Geiger Muller to measure the dose to the irradiation distance or collimation area and can be used as a reference for further research in this field.